Financing patterns: Measurement concepts and empirical results - Andreas Hackethal; Reinhard H. Schmidt (Johann Wolfgang Goethe-Universität Frankfurt am Main, Fachbereich Wirtschaftswissenschaften, 2000)
A widely recognized paper by Colin Mayer (1988) has led to a profound revision of academic thinking about financing patterns of corporations in different countries. Using flow-of-funds data instead of balance sheet data, Mayer and others who followed his lead found that internal financing is the dominant mode of financing in all countries, that therefore financial patterns do not differ very much between countries and that those differences which still seem to exist are not at all consistent with the common conviction that financial systems can be classified as being either bank-based or capital market-based. This leads to a puzzle insofar as it calls into question the empirical foundation of the widely held belief that there is a correspondence between the financing patterns of corporations on the one side, and the structure of the financial sector and the prevailing corporate governance system in a given country on the other side. The present paper addresses this puzzle on a methodological and an empirical basis. It starts by demonstrating that the surprising empirical results found by Mayer et al. are due to a hidden assumption underlying their methodology. It then derives an alternative method of measuring financing patterns, which also uses flow-of-funds data, but avoids the questionable assumption. This measurement concept is then applied to patterns of corporate financing in Germany, Japan and the United States. The empirical results are very much in line with the commonly held belief prior to Mayer's influential contribution and indicate that the financial systems of the three countries do indeed differ from one another in a substantial way.
urn:nbn:de:hebis:30-17822
Keywords: 330; Kapitalstruktur; Kapitalflussrechnung; Finanzsystem; Corporate Governance; Theorie; Deutschland; USA; Japan